Asperger meets girl : happy endings for Asperger boys - Griffiths, Jonathan, 1968- (Jessica Kingsley Publishers, 2008)
Men with Asperger's Syndrome, young and old, experience difficulty with social interaction, which can be a stumbling block when it comes to getting a girlfriend. Here is a book that demystifies the enigma of 'relationships' by explaining everything in Asperger-friendly terms (some of them mathematical, naturally). Asperger Meets Girl provides hope for all hopeless wooers by offering a choice of three interrelated abstract models for understanding boy-girl relationships. And, to make life easier, these models are presented in graph form where possible. The book also gives valuable practical tip.